Characterization of Electrode with Cu2O-ZnO/C and Pt-Ru/C Catalyst for Electrochemical Reduction CO2 to CH3OH - Dea Radestia Rahmah; Dedi Rohendi; Nirwan Syarif; Addy Rachmat; Nyimas Febrika Sya'baniah; Dwi Hawa Yulianti (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
Electrode characterization has been carried out with Cu2O-ZnO/C and Pt-Ru/C catalysts to convert carbon dioxide to methanol. Characterization are carried out with XRD analysis, Cyclic Voltammetry (CV) and Electrochemical Impedance Spectroscopy (EIS). The electrodes are made by distributing Cu2O-ZnO/C and/or Pt-Ru/C catalyst by spraying method. The results of XRD analysis showed that the characteristic peak of platinum was 2θ = 39.7⁰ - 40.74⁰ with an intensity of 970 cps and 1384 cps and the diffraction peak of Ru oxide was found at 47.02⁰ with an intensity of 923 cps. The peak of Cu2O characteristics appeared at 36.12⁰ with an intensity of 88 cps and the peak for ZnO characteristics at 68.2⁰ with an intensity of 13 cps. The test results with the cyclic voltammetry method showed that the electrode with a Cu2O-ZnO/C catalyst obtained the highest ECSA value which was 26.044 cm2/g, with an electrical conductivity value of 3.4 x 10-3 S/cm and a total real resistance of 5.9425 Ω .